Manajemen Strategi Galeri Investasi Syariah untuk Meningkatkan Minat Mahasiswa dalam Berinvestasi di Pasar Modal Syariah - Leni Afrina; Eja Armaz Hardi; Fauzan Ramli (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
This research discusses GIS strategic management to increase students' interest in investing in the Islamic capital market. Based on the data, it can be seen that the number of investors in the GIS of UIN STS Jambi since the establishment of GIS 2016-2022, the number of investors each year is unstable and is still relatively low. However, as time goes by, some investors are no longer active in stock trading. This is due to investors' ignorance of the Islamic capital market. The results of this research are that the management strategy used is KSPM discussion, socialization, group formation, implementing the Sharia Capital Market School (SPMS) after that Sharia Capital Market Activation (APMS). The problems faced by GIS include administrators who are less active in carrying out GIS programs and activities, lack of awareness of FEBI students to see investment opportunities, difficulty in inviting FEBI students to take part in activities at GIS.